O supervisor de ensino: atuação na educação especial - Rustichelli, Deise de Sales (2015)
The present paper searches into the performance of teaching supervisors in the special education from special classes to resource rooms. Discusses the supervisory action by analyzing the gathered information collected in data forms visit by the teaching supervisors in special classes and in resources rooms of two schools which ones count on those services of educational specialized support (SAPE-s) in network state schools inner São Paulo, at the lapse of time when the change from the special classes to the resource rooms happened (2000-2013) and searches to know, through semi-structured interviews with specialized teachers and teaching supervisors, how do they position themselves in relation to the inclusion of students classified as Intellectually Disabilited ( DI), to the ways of forwarding students to specialized treatment and teaching supervisor's performance in special education. Through a literature search, based on the Historical-Critical Pedagogy, we conducted a historical of the teaching supervision, placing its performance in the history of special education, since the appearence of special classes up to the inclusion movement from the Salamanca Statement and problematize a reality permeated by contradictions in that inclusive education is understood as a justification to classify a large number of students as intellectually disabilited (ID). The analysis of the data forms visit, interviews, legal documents and standards that rule the network state special education system allowed us to understand that discrimination and labeling of students who present learning difficulties are factors that embarasses the student classified as DI to enjoy the right to education, to which everyone, without exception, should enjoy.